Differences in Diffusion Tensor Imaging White Matter Integrity Related to Verbal Fluency Between Young and Old Adults - Yeske, Benjamin; Hou, Jiancheng; Adluru, Nagesh; Nair, Veena A.; Prabhakaran, Vivek (Frontiers in Aging Neuroscience, 2021)
Throughout adulthood the brain undergoes an array of structural and functional changes during the typical aging process. These changes involve decreased brain volume, reduced synaptic density, and alterations in white matter. While there have been some previous neuroimaging studies that have measured adult language production ability and its correlations to brain function, structural gray matter volume, and functional differences across young and old adults, the structural role of white matter in adult language production in individuals across the lifespan remains to be thoroughly elucidated. The present study recruited 38 young adults and 35 old adults for diffusion tensor imaging (DTI) and to perform the Controlled Oral Word Association Test to assess verbal fluency (VF). Tract-Based Spatial Statistics were employed to evaluate voxel-based group differences of diffusion metrics for the values of fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD), radial diffusivity (RD) and Local Diffusion Homogeneity (LDH) in 12 white matter regions of interest associated with language production. To investigate group differences on each DTI metric an ANCOVA controlling for sex and education level was performed, and the statistical threshold was considered p < 0.00083 (0.05/60 labels) after Bonferroni correction for multiple comparisons. Significant DTI metrics identified in the ANCOVA were used to perform correlation analyses with VF scores. Compared to the old adults, the young adults had significantly: (1) increased FA values on the anterior corona radiata (ACR) bilaterally; (2) decreased MD values on the right ACR, but increased MD on the left uncinate fasciculus (UF); (3) decreased RD on the ACR bilaterally. There were no significant differences between groups for AD or LDH. Moreover, the old adults had only a significant correlation between the VF score and the MD on the left UF. There were no significant correlations between VF score and DTI metrics in young adults. This study adds to the growing body of research that white matter areas involved in language production are sensitive to aging.